The Effect of Long-Term Intranasal Serotonin Treatment on Metabolic Parameters and Hormonal Signaling in Rats with High-Fat Diet/Low-Dose Streptozotocin-Induced Type 2 Diabetes - Kira V. Derkach; Vera M. Bondareva; Oxana V. Chistyakova; Lev M. Berstein; Alexander O. Shpakov (International Journal of Endocrinology)
In the last years the treatment of type 2 diabetes mellitus (DM2) was carried out using regulators of the brain signaling systems. In DM2 the level of the brain serotonin is reduced. So far, the effect of the increase of the brain serotonin level on DM2-induced metabolic and hormonal abnormalities has been studied scarcely. The present work was undertaken with the aim of filling this gap. DM2 was induced in male rats by 150-day high-fat diet and the treatment with low dose of streptozotocin (25 mg/kg) on the 70th day of experiment. From the 90th day, diabetic rats received for two months intranasal serotonin (IS) at a daily dose of 20 μg/rat. The IS treatment of diabetic rats decreased the body weight, and improved glucose tolerance, insulin-induced glucose utilization, and lipid metabolism. Besides, it restored hormonal regulation of adenylyl cyclase (AC) activity in the hypothalamus and normalized AC stimulation by β-adrenergic agonists in the myocardium. In nondiabetic rats the same treatment induced metabolic and hormonal alterations, some of which were similar to those in DM2 but expressed to a lesser extent. In conclusion, the elevation of the brain serotonin level may be regarded as an effective approach to treat DM2 and its complications.